2021
DOI: 10.3390/foods10030581
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Lead and Cadmium in Some Food Supplements Available on the Romanian Market

Abstract: Across the world, there has been an increase in the consumption of food supplements. This may be due to the perception that these dietary supplements cannot negatively affect the health of consumers in any way. However, dietary supplements may not have the expected effect. In addition, it has been shown that supplements can sometimes be chemically, physically or microbiologically contaminated, if the hygiene conditions and Hazard Analysis Critical Control Points (HACCP) plan are not fully complied with. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our results are in accordance with findings of other studies conducted in order to assess potential human risks associated with mussel consumption in the region of Black Sea [54][55][56]. It should be noted also that calculated hazard quotients for investigated heavy metals within the current research were higher than values found in other investigated food categories in Romania (honey, food supplements) [57,58].…”
Section: Estimated Risk Through Mussel Consumptionsupporting
confidence: 91%
“…Our results are in accordance with findings of other studies conducted in order to assess potential human risks associated with mussel consumption in the region of Black Sea [54][55][56]. It should be noted also that calculated hazard quotients for investigated heavy metals within the current research were higher than values found in other investigated food categories in Romania (honey, food supplements) [57,58].…”
Section: Estimated Risk Through Mussel Consumptionsupporting
confidence: 91%
“…This can also be achieved by adding flour obtained from mixing wheat flour with flour from various plants that have a high mineral content. Current cereal breeding programs are mainly focused on higher yields and higher technological quality for industrial processing, neglecting health and nutritional aspects, including possible allergenic factors that may emanate from substances used to increase productivity and control pests [57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium (Cd 2+ ) and lead (Pb 2+ ) are considered two of the most hazardous elements that can be easily accumulated in water, soil, food, and the human body ( Mustatea, Ungureanu, Iorga, Ciotea, & Popa, 2021 ). An excess level of Cd and Pb in food can cause several serious diseases to humans, including kidney damage, central nervous system disease, or even cancer ( Li and Zhang, 2021 , Moon et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%